2022
DOI: 10.1038/s41550-022-01713-z
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature nitrogen-bearing polycyclic aromatic hydrocarbon formation routes validated by infrared spectroscopy

Abstract: The following full text is an Author's version preprint which may differ from the publisher's version.For additional information about this publication click this link. https://repository.ubn.ru.nl/handle/2066/253669Please be advised that this information was generated on 2023-01-02 and may be subject to change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 61 publications
1
25
0
Order By: Relevance
“…Notably, the same model generally reproduces the observed abundances of linear and mono-cyclic nitriles 3 , but underpredicts the abundance of bicyclic indene by four orders of magnitude 4 . Laboratory studies have shown that nitrogen bearing aromatic molecules 5 , as well as pure hydrocarbons like naphthalene 6 and indene 4 , 7 , may be readily formed in barrierless, gas-phase ion-molecule and radical-molecule reactions under conditions similar to those in interstellar clouds. On the other hand, the model of McGuire et al indicates rapid depletion of CNN from TMC-1 through interactions with ions, 3 and it predicts a limited abundance of its main precursor, naphthalene, which has also been shown to be a keystone in the formation of larger PAHs 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the same model generally reproduces the observed abundances of linear and mono-cyclic nitriles 3 , but underpredicts the abundance of bicyclic indene by four orders of magnitude 4 . Laboratory studies have shown that nitrogen bearing aromatic molecules 5 , as well as pure hydrocarbons like naphthalene 6 and indene 4 , 7 , may be readily formed in barrierless, gas-phase ion-molecule and radical-molecule reactions under conditions similar to those in interstellar clouds. On the other hand, the model of McGuire et al indicates rapid depletion of CNN from TMC-1 through interactions with ions, 3 and it predicts a limited abundance of its main precursor, naphthalene, which has also been shown to be a keystone in the formation of larger PAHs 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, ion−molecule reactions are considered to play an important role in the growth of nitrogen- bearing PAHs in space. 44 This study also would broaden our knowledge of the evolution of complex organic molecules through ion−molecule reactions in space.…”
Section: T H Imentioning
confidence: 93%
“…These gaseous ion–molecule reactions may also occur in extraterrestrial space with the related interstellar molecules ionized by cosmic rays or internal ultraviolet photons. Very recently, ion–molecule reactions are considered to play an important role in the growth of nitrogen-bearing PAHs in space . This study also would broaden our knowledge of the evolution of complex organic molecules through ion–molecule reactions in space.…”
mentioning
confidence: 87%
“…Following the chemical rules for aromaticity, the PAH interstellar formation mechanisms, nitrogen, which is isoelectronic with CH, can be substituted for carbon atoms, forming polycyclic aromatic nitrogen heterocycles (PANHs). Nitrogen insertion may be an important phenomenon in the PAH life cycle that affects the emission profiles and positions significantly . PANHs can help in explaining the 6.2 μm (6200 nm) profile as well as other features very well. , The constraints of cosmic abundance stipulate that the interstellar PAH population could include PANHs in a significant amount. , The detection of PANHs in carbonaceous meteorites and in the form of PAH nitriles , in TMC-1, a molecular cloud, suggests their significant presence in the ISM.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen insertion may be an important phenomenon in the PAH life cycle that affects the emission profiles and positions significantly. 45 PANHs can help in explaining the 6.2 μm (6200 nm) profile as well as other features very well. 46,47 The constraints of cosmic abundance stipulate that the interstellar PAH population could include PANHs in a significant amount.…”
Section: ■ Introductionmentioning
confidence: 99%